Sense of purpose in life and subjective cognitive failures. (January 2023) - Sutin, Angelina R.; Aschwanden, Damaris; Luchetti, Martina; Stephan, Yannick; Terracciano, Antonio
Abstract: A greater sense of purpose in life is an aspect of well-being associated with markers of cognitive health across adulthood, including subjective cognition. The current research extends this work to examine how purpose is associated with cognitive failures, which are momentary lapses in cognitive function, whether this association varies by age, sex, race, or education, and whether it is accounted for by depressed affect. Adults across the United States ( N  = 5100) reported on their sense of purpose in life, recent cognitive failures in four domains (memory, distractibility, blunders, names), and depressed affect. Purpose was associated with fewer cognitive failures overall and within each domain (median d  = 0.30, p < .01), controlling for sociodemographic covariates. These associations were similar across sex, education, and racial groups but were stronger at relatively older than younger ages. Depressed affect accounted for all the association between purpose and cognitive failures among adults younger than 50; the association was reduced by half but remained significant among participants 50 and older. Purpose was associated with fewer cognitive failures, especially in the second half of adulthood. Purpose may be a psychological resource that helps support subjective cognition among relatively older adults, even after accounting for depressed affect.